Organizational Reflection and Its Impact on Strategic Performance: An Analytical Research in the General Company for Electrical and Electronic Industries - misanjas misanjas; Ayman Abdul Sattar Jasim; Aamer Fadous Azib Al-Lami ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Technology companies try to ensure that their products stay in the market longer by understanding the needs of their customers. This Research examined organizational psychology and organizational performance variables, focusing on dimensions of organizational psychology (organizational knowledge, organizational analysis, creative thinking, and organizational improvement) and dimensions of organizational performance (business performance, competitiveness). internal employment, and economic growth). A large contractor from the power and electricity sectors was selected as a case Research. The research problem focused on the outcomes of organizational psychology that contribute significantly to enhancing strategic performance, understanding employee perceptions of these two dimensions, and examining the relationships between the variables. The results concluded that the company places great emphasis on organizational awareness as an important factor in improving its products and that there is a significant relationship between organizational mindset and strategy.